2019
DOI: 10.1111/ocr.12333
|View full text |Cite
|
Sign up to set email alerts
|

Forces and moments generated by aligner‐type appliances for orthodontic tooth movement: A systematic review and meta‐analysis

Abstract: The aim of this review was to systematically appraise the evidence on aligner mechanics and forces and moments generated across difference types of aligners. In vitro‐ laboratory studies for model simulated tooth movement with aligners. Database searches within Medline via Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL), LILACS via BIREME Virtual Health Library. Unpublished literature was also searched in Open Grey, ClinicalTrials.gov (http://www.clinicaltrials.gov), the National Research Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 21 publications
3
37
0
5
Order By: Relevance
“…Studies evaluated in the three groups were chemical applications, surgical applications and mechanical-physical applications. Agents such as acetyl salicylic acid 35 , 1,25-dihydroxycholecalciferol [7][8] , nitric oxide 9 , thyroid hormones 10 , and cortisone 11 , as well as prostaglandins have been used in the type of studies 12 . As surgical applications, corticotomy and similar applications are among the studies carried out to accelerate the orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluated in the three groups were chemical applications, surgical applications and mechanical-physical applications. Agents such as acetyl salicylic acid 35 , 1,25-dihydroxycholecalciferol [7][8] , nitric oxide 9 , thyroid hormones 10 , and cortisone 11 , as well as prostaglandins have been used in the type of studies 12 . As surgical applications, corticotomy and similar applications are among the studies carried out to accelerate the orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, it was observed that molars 19,20,23,24,[26][27][28][29]42,43 and incisors 7,25,35,[44][45][46] were used for experimental orthodontic tooth movement. However, Altan et al 25 used only incisors in rat studies in which low-dose laser was examined for experimental orthodontic tooth movements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação à eficácia do tratamento, revisões sistemáticas sugeriram que essa modalidade de tratamento apresenta algumas dificuldades em movimentos ortodônticos específicos quando comparados a aparelhos fixos (Buschang et al, 2014, Djeu, 2005, Kuncio et al, 2007. De forma controversa e graças às propriedades mecânicas satisfatórias e aos avanços da tecnologia dos alinhadores, atualmente essa terapia é adequada para a correção de um amplo espectro de más oclusões (Beers et al, 2003), estudos tem observado que tanto o uso dos sistemas invisíveis quanto de aparelhos fixos tem fornecido resolução significativa no tratamento ortodôntico, considerando suas especificidades e indicações de tratamento (Balachandran, Ganapathy & Ramanatha, 2019, Iliadi, Koletsi &Eliades, 2019 .…”
Section: Tratamento Ortodôntico Invisível Comparado Com Os Sistemas Funclassified
“…The majority of manufacturers have changed the initially utilized thermoplastic material with polyethylene terephthalate glycol (PETG) and fabricate aligners of variable thicknesses. Regardless of the chemical compositions of the raw material used, the biomechanics [8][9][10] and the mode of action behind aligners remain similar. Specifically, every positioner is subject to deformation upon intraoral placement, and the initial magnitude of force placed on the teeth depends both on material stiffness and thickness as well as the intended tooth displacement prescription [11,12].…”
Section: Introductionmentioning
confidence: 99%